1999
DOI: 10.2307/3454475
|View full text |Cite
|
Sign up to set email alerts
|

Polychlorinated Biphenyls and Methylmercury Act Synergistically to Reduce Rat Brain Dopamine Content in Vitro

Abstract: Consumption of contaminated Great 1Las fish by pregnant women is associated with decreased birth weight and deficits in cognitive function in their infants and children. These fish contain many known and suspected anthropogenic neurotoxicants, makdig it difficult to determine which contaminant(s) are responsible for the observed deficits. We have undertaken a series of experiments to determine the relevant toxicants by comparing the neurotouic efifect of two of these contaminants-polychorinated biphenyls (PCBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…Although we did not use enough different concentrations for the doses to statistically distinguish between additive or synergistic effects, the present data plus our earlier data on PCB 153 and MeHg suggest that PCB 153 and MeHg can act synergistic in the low-dose range, but not in the high dose range. This is in agreement with the in vitro studies by Bemis and Seegal (1999) that have shown significantly altered dopamine concentrations from coexposure to PCB plus MeHg compared to PCB alone or MeHg alone.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although we did not use enough different concentrations for the doses to statistically distinguish between additive or synergistic effects, the present data plus our earlier data on PCB 153 and MeHg suggest that PCB 153 and MeHg can act synergistic in the low-dose range, but not in the high dose range. This is in agreement with the in vitro studies by Bemis and Seegal (1999) that have shown significantly altered dopamine concentrations from coexposure to PCB plus MeHg compared to PCB alone or MeHg alone.…”
Section: Discussionsupporting
confidence: 93%
“…Interactions between PCB and MeHg have been shown to act synergistically on the dopamine content in striatal brain punches in vitro studies (Bemis and Seegal, 1999). Recent in vivo studies indicate that developmental co-exposure of rats both to an ortho-substituted PCB (PCB 153) and MeHg can induce motor behavioral defects (Roegge et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Both are fish contaminants, and the possibility of an interaction, leading to synergistic adverse effects, had been suggested by earlier experiments in vitro and in animals (Bemis and Seegal, 1999;Roegge et al, 2004), and by observations in humans (Grandjean et al, 2001;Stewart et al, 2003). By utilizing an effect additivity approach, as indicated by Lau et al (2006), we found no interactions among MeHg, PCB 126 and PCB 153 (Fig.…”
Section: Mehgsupporting
confidence: 48%
“…(2) To assess possible interactions between MeHg and PCBs. This was prompted by epidemiological, animal, and in vitro evidence which suggested a possible synergistic interaction between these compounds (Grandjean et al, 2001;Bemis and Seegal, 1999;Roegge et al, 2004). (3) To determine whether neurons with genetically modified glutathione (GSH) levels may be exploited as a screening tool for further mechanistic studies.…”
Section: Introductionmentioning
confidence: 99%
“…Polychlorinated biphenyl and MeHg act synergistically on the DA content in striatal brain punches in vitro (Bemis and Seegal 1999). Exposure to the PCB mixtures A1254 and A1260 (10-200 ppm) only, reduced tissue DA and elevated media DA in a dose-dependent fashion.…”
Section: Effects On the Neurotransmitter Systemmentioning
confidence: 94%